2005
DOI: 10.1002/mds.20634
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic tremor disorders identified using tree‐based statistical algorithms and quantitative tremor analysis

Abstract: Detecting psychogenic tremors (PsychT) is often challenging. As there are no laboratory investigations or imaging techniques that can confirm the diagnosis, PsychT is identified on a clinical basis. We present a tree-based statistical algorithm derived from quantitative computerized tremor recordings as a novel method to help in the recognition of PsychT. The goal of this study was to show that objective data from computerized tremor recordings, when processed through a tree-based statistical algorithm, can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…The investigators also noted that the absence of finger tremor was more compatible with PT when compared to organic tremor. Although tremorgraphic recordings and neurophysiological techniques may enhance the differentiation of ET and PT, [30][31][32][33] most physicians do not have access to this technology and must rely on clinical findings. There is no consensus at this time about the best treatment of PT, but the development of a PMD rating scale is an important step in the validation of therapeutic strategies [34].…”
Section: Discussionmentioning
confidence: 98%
“…The investigators also noted that the absence of finger tremor was more compatible with PT when compared to organic tremor. Although tremorgraphic recordings and neurophysiological techniques may enhance the differentiation of ET and PT, [30][31][32][33] most physicians do not have access to this technology and must rely on clinical findings. There is no consensus at this time about the best treatment of PT, but the development of a PMD rating scale is an important step in the validation of therapeutic strategies [34].…”
Section: Discussionmentioning
confidence: 98%
“…47,87,88 Relatively consistent physiologic findings include an increase in tremor amplitude with inertial loading (Figure 7), large fluctuations in frequency and amplitude, co-activation of antagonist muscles at the onset of tremor, and the absence of finger tremors. [89][90][91] Coexistent non-physiologic signs such as weakness or sensory abnormalities and underlying psychopathology can also help to suggest the diagnosis. Because it may be difficult to approach patients with a diagnosis of psychogenic tremor, clinicians are often reluctant to discuss the possibility of psychogenicity.…”
Section: Psychogenic Tremormentioning
confidence: 99%
“…EMG has been used to distinguish muscle activation depending on the neurological disease [ 70 72 ]; for example, Nisticò and Vescio et al [ 73 , 74 ] showed that during rest tremor, the activation of antagonist muscles is synchronous in subjects with ET and alternating in those with PD. EMG and accelerometer/IMU combinations [ 75 83 ] have been extensively used to discriminate PD, ET [ 84 89 ], physiological tremor (PH) [ 90 , 91 ], psychogenic tremor [ 92 , 93 ], advanced ET [ 94 ], and MS [ 95 ] from each other by using ML techniques on DWT and HT signal decomposition during, in its majority, stretch and steady positions. MMG [ 96 ] was recently used with EMG, force sensors, and IMUs to detect tremor differences in PD after deep brain stimulation [ 97 ].…”
Section: Technologies For Tremor Assessmentmentioning
confidence: 99%